Стиль блюз в музыке - Карловна Зарифян, Наринэ (Musical Armenia, 2010)
Composer, Yerevan State Conservatory after komitas, associate professor Naira Carli Zarifyan’s historical excursus into the “blues style in music” analytical article. Author presents the formation of blues, its influence on “not jazz” composers’ art. To blues have referred K.Debyusi, I. Stravinsky, E. Sati, M. Ravely, F. Pulenc and others. Author reveals in details the stages of development of the blues, increasing structural peculiarities. Referred to the art of famous blues performers, musicians.